МОНГОЛ ДАХЬ ОРОН НУТГИЙН ХУРЛЫН СОНГУУЛИЙН ТҮҮХЭН ХӨГЖИЛ - М.Жавзансүрэн (Politology, 2023)
The research covers the history of local administrative organizations so called public assembly, labourer’s public assembly, labour representative’s assembly, public representative’s assembly and historical development of their structure and legal status. The main of our study is an election system and how it was formed of and developed. During the People’s Revolution of 1921, election system was reflected in documents. And it was enacted by constitution of Mongolia in 1924 and had been developed until 1990.